2004
DOI: 10.1108/14626000410519100
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with formal networking in regional small business: some findings from a study of Swedish SMEs

Abstract: A number of recent studies have suggested that, for small businesses to compete with their larger counterparts in the electronic commerce environment, many are collaborating in a network arrangement. This study examines whether factors such as business size, business age, business sector or market focus are associated with decisions to collaborate in a network or remain outside such arrangements. The study showed that small businesses, with fewer than ten employees, were more likely to be part of a formal netw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
1
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(58 citation statements)
references
References 63 publications
1
54
1
2
Order By: Relevance
“…The small firm is generally an extension of the beliefs, attitudes, and behaviours of the entrepreneur or owner-manager. This means that SMEs are strongly influenced by their owners' personal idiosyncrasies (MacGregor, 2004). Therefore, the beliefs, attitudes, and behaviours of the owner-manager will define the SME's learning culture.…”
Section: Organization-related Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…The small firm is generally an extension of the beliefs, attitudes, and behaviours of the entrepreneur or owner-manager. This means that SMEs are strongly influenced by their owners' personal idiosyncrasies (MacGregor, 2004). Therefore, the beliefs, attitudes, and behaviours of the owner-manager will define the SME's learning culture.…”
Section: Organization-related Factorsmentioning
confidence: 99%
“…The decision to adopt and use IT innovation is made easier in a networked environment (MacGregor, 2004), as organizations within this environment will exert pressures towards IT innovation adoption. They will as well provide assistance to each other, allowing SMEs within the network to overcome their resource limitations (Mohnnak, 2007).…”
Section: Institutional Factorsmentioning
confidence: 99%
“…This question tries to determine whether organisational size influences the level of ICT adoption (MacGregor, 2004). MacGregor (2004) has found that smaller firms lack the skills and capital to be high level adopters.…”
Section: Size Of Your Business In Terms Of Employees and Annual Turnomentioning
confidence: 99%
“…MacGregor (2004) has found that smaller firms lack the skills and capital to be high level adopters.…”
Section: Size Of Your Business In Terms Of Employees and Annual Turnomentioning
confidence: 99%
“…The main concern in this study is the importance of education in increasing consumer awareness of online purchasing and the benefits of such purchasing to a wide sector ( [73], [85], [86]). The results of this study indicate the importance of educational level to spreading awareness of online purchasing through smartphone application in the GCC societies.…”
Section: Education Level Characteristicsmentioning
confidence: 99%